Design Strategies for Houses Subject to Heatwaves - Bennetts, Helen; Pullen, Stephen; Zillante, George (Open house international, 2012)
Over the last two decades the average floor area of new houses in Australia has increased significantly. This has coincided with greater expectations of thermal comfort in homes. In certain locations, the result has been an escalation of the use of large mechanical air conditioning systems in houses. Since it is predicted that climate change will lead to an increase in the frequency and severity of extreme weather events such as heatwaves, the future maintenance of thermal comfort in houses in an affordable manner is likely to be challenging. This will have implications not only for the health and comfort of the occupants but also for peak energy loads. A compounding factor is the likelihood of increased energy prices caused, in part, by financial mechanisms aimed at minimising greenhouse gas emissions. There will be sections of the community, such as the elderly and the less well off, that will be particularly vulnerable to these combined factors. This paper explores design strategies that could be incorporated in new and existing houses to improve thermal comfort for residents during heatwaves. It is shown that during such periods, behaviour change, thermal comfort requirements and extra energy consumption have a strong influence on devising solutions for this challenge. The results of a pilot study are given that indicate opportunities for creating cool refuges in the existing dwelling stock.